2017
DOI: 10.2217/bmm-2017-0152
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MTAP Expression is a Negative Prognostic Marker in Ewing Sarcoma Family of Tumors

Abstract: Loss of MTAP expression is an independent negative prognostic biomarker in ESFT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Others: Machado et al found that when MTAP expression was lost in ES, the overall survival was shorter [53] . Naranjo et al found that high ERBB4 expression is associated with metastatic disease in ES patient samples [54] .…”
Section: Resultsmentioning
confidence: 99%
“…Others: Machado et al found that when MTAP expression was lost in ES, the overall survival was shorter [53] . Naranjo et al found that high ERBB4 expression is associated with metastatic disease in ES patient samples [54] .…”
Section: Resultsmentioning
confidence: 99%
“… 4 Therefore, researchers are paying more and more attention to the predictive function of characteristic molecular markers for EWS patient prognosis. The existing studies have examined the expression of genes, such as SOX2, MTAP, and Connexin, and their relationship to outcomes in patients with EWS, 21 , 22 , 23 yet no clinically available marker or an actual target for therapy has emerged from those investigations. One of the goals in EWS treatment is to find prognostic or predictive biomarkers that will be able to guide therapeutic decisions and serve as targets for novel therapies.…”
Section: Discussionmentioning
confidence: 99%
“…For pediatric gliomas, MTAP were more frequent in grade IV gliomas (62.5%, p = 0.0087) but rare in grade I gliomas (12.2%, p = 0.0178); besides, MTAP gene deletion was correlated with a poor survival (p = 0.01) and a shorter PFS (p = 0.016) 26 . The results from the Ewing sarcoma family of tumors also revealed loss of MTAP expression was a negative prognostic marker 27 . The present study was consistent with previous studies, that the shorter survival (p = 0.044) and PFS (p = 0.002) were in patients with MTAP low expression, even though they were more sensitive to pemetrexed than patients with MTAP high expression.…”
Section: Variablesmentioning
confidence: 99%